2009
DOI: 10.1185/03007990902994041
|View full text |Cite
|
Sign up to set email alerts
|

Three-month, randomized, parallel-group comparison of brimonidine–timolol versus dorzolamide–timolol fixed-combination therapy

Abstract: Fixed-combination brimonidine-timolol provided the same or greater IOP lowering compared with fixed-combination dorzolamide-timolol. Both fixed-combination medications were safe and well-tolerated. Brimonidine-timolol received higher ratings of ocular comfort than dorzolamide-timolol. The duration of the studies was 3 months, and additional studies will be needed to compare the efficacy and tolerability of brimonidine-timolol and dorzolamide-timolol during long-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
28
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 17 publications
6
28
1
2
Order By: Relevance
“…Although most previously published daytime studies 28,29 have demonstrated similar IOP-lowering efficacy for BTFC over DTFC, a recent 3-month parallel-arm study by Nixon et al 38 reported a greater IOP reduction with BTFC monotherapy (À7.7 mm Hg) compared with DTFC monotherapy (À6.7 mm Hg). The study by Nixon et al 38 pooled data from two separate trials: a single site pilot study with 40 patients, and a multi-centre trial with 140 patients.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Although most previously published daytime studies 28,29 have demonstrated similar IOP-lowering efficacy for BTFC over DTFC, a recent 3-month parallel-arm study by Nixon et al 38 reported a greater IOP reduction with BTFC monotherapy (À7.7 mm Hg) compared with DTFC monotherapy (À6.7 mm Hg). The study by Nixon et al 38 pooled data from two separate trials: a single site pilot study with 40 patients, and a multi-centre trial with 140 patients.…”
mentioning
confidence: 94%
“…Out of the total of 180 patients, 101 were treated with BTFC or DTFC as monotherapy (30 from the pilot study, 71 from the multi-centre trial), whereas 79 patients were treated as an adjunct to prostaglandin therapy. 38 The methodology of that study was critically differed from the protocol utilised in the present study in several ways. First, the Nixon study 38 measured IOP at a single time point (1000) at 2 h post dose.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Возможно и рекомендуется использование комби-нированных медикаментозных средств, однако гипотен-зивный эффект наступает не всегда [15,16]. Проведение лазерных вмешательств на радужке и углу передней ка-меры затруднено из-за выраженного рубеоза (неоваску-ляризации) этих структур [17].…”
unclassified